Strengthening Moderate Islamic Insight in Madrasah through Integration of Islamic Education Curriculum - Sholikah, Sholikah; Latif, Isnawati Nur Afifah (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
This research aims to explain the construction of moderate Islamic curriculum integration at Madrasah and the output of moderate Islamic curriculum integration. This research used a qualitative approach with the MI Nurul Islam Gresik as the research location. The data collection used observation, interviews, and documentation, while data analysis used qualitative and content analysis. This research found that the construction of the integration of the Moderate Islamic curriculum at MI Nurul Islam Gresik is, first, through formal activities through teaching and learning activities that support the cultivation of moderate Islamic values, including religion, social care, example, tolerance, religion, social care, tolerance; second, through non-formal/extras that support the cultivation of moderate Islamic values including democracy and social care; third, through examples that support the cultivation of moderate Islamic values, which include: social care, cooperation, and religion; and fourth, through habits that support the cultivation of moderate Islamic values including religion, tolerance, democracy, social care, social concern. Meanwhile, the outputs from the integration of the moderate Islamic curriculum at MI Nurul Islam Gresik are first, creating a religious student character; second, creating a tolerant student character; third, creating student characters who care about others; fourth, creating student characters who love peace; fifth, creating student characters who like deliberation. The theoretical implication of the research is that curriculum integration in education can give birth to a new educational curriculum model that is adaptive to current developments following sociological conditions and demographic locations.